The acquisition of English 'be' auxiliary and thematic verb constructions by adult Arab ESL learners. - Yahya Ali Muftah, Muneera; Wong, Bee Eng (Canadian Center of Science and Education, 2011)
This study investigates the acquisition of English be auxiliary and thematic verb constructions in non-past contexts by adult Arab learners of English as a Second Language (ESL). It is well known that second language (L2) learners show variability in the L2 production of verbal inflectional morphology by either omitting inflections or marking inappropriate substitution of one kind of inflection for another. The Missing Surface Inflection Hypothesis (MSIH) (Prévost and White, 2000) proposes that L2 learners have knowledge of functional categories and features underlying tense and agreement although sometimes they fail to produce the corresponding overt forms. In order to examine the nature of the adult Arab ESL learners’ interlanguage (IL) grammar at the L2 ultimate attainment level as well as the extent to which the learners can acquire English be auxiliary and thematic verb constructions in non-past contexts, an oral production task (ORPT) was conducted with 77 adult Arab ESL learners subdivided into three proficiency levels (lower-intermediate, upper-intermediate and advanced). An analysis of the ORPT show that the L2 learners omit and wrongly use the be auxiliary verbal inflection (am, is, are) more frequently than the thematic verb inflection (-s) in their production. The results reveal that the adult Arab ESL learners, even at ultimate attainment level, are more sensitive to the thematic verb contractions than to the be auxiliary constructions. These results suggest that variability in the production of verbal inflectional morphology is due to problems with the realization of surface morphology in accordance with the MSIH.